2004
DOI: 10.1074/jbc.m311301200
|View full text |Cite
|
Sign up to set email alerts
|

Mlx Is the Functional Heteromeric Partner of the Carbohydrate Response Element-binding Protein in Glucose Regulation of Lipogenic Enzyme Genes

Abstract: The expression of genes encoding enzymes involved in de novo triglyceride synthesis (lipogenesis) is transcriptionally induced in the liver in response to increased glucose metabolism. The carbohydrate response element-binding protein (ChREBP) is a newly identified basic helix-loop-helix/leucine zipper transcription factor proposed to regulate the expression of the glucoseresponsive gene pyruvate kinase. This gene contains a carbohydrate response element (ChoRE) consisting of two E box motifs separated by 5 bp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
185
0
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 192 publications
(203 citation statements)
references
References 42 publications
(51 reference statements)
11
185
0
4
Order By: Relevance
“…Hence, 14-3-3 proteins appear to be important regulators of the Mlx-driven transcription factor (this work and 32). The regulation of glucose metabolism by Wbscr14 supports the hypothesis that the diabetic phenotype observed in WBS patients could be related to WBSCR14 hemizygosity (5,6,9,14,57). The hemizygosity of this transcription factor could reduce its ability to respond to high-glucose diet through activation of the expression of enzymes involved in de novo triglycerides synthesis using glucose precursors.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Hence, 14-3-3 proteins appear to be important regulators of the Mlx-driven transcription factor (this work and 32). The regulation of glucose metabolism by Wbscr14 supports the hypothesis that the diabetic phenotype observed in WBS patients could be related to WBSCR14 hemizygosity (5,6,9,14,57). The hemizygosity of this transcription factor could reduce its ability to respond to high-glucose diet through activation of the expression of enzymes involved in de novo triglycerides synthesis using glucose precursors.…”
Section: Discussionsupporting
confidence: 61%
“…Conversely, glucagon and fatty acids increase the level of AMP and cAMP in hepatocytes activating AMPK and/or PKA, which results in the phosphorylation of WBSCR14 at residue Ser 568 and inhibition of its DNA-binding activity (5,6,9,12). Recent observations demonstrated that rat WBSCR14 plays also an essential role in the regulation of other lipogenic enzymes, besides LPK, involved in glucose and lipid metabolism (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…3B). ChREBP is thought to be the primary glucose-responsive transcription factor that governs the expression of glycolytic and lipogenic genes (6,9). Similar to the other lipogenic transcription factors, ACSL3 knockdown suppressed ChREBP reporter gene activity (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Overexpressing ChREBP in primary hepatocytes induces activity of the ChoRE-containing PK promoter in high glucose conditions but not in low glucose conditions (20). However, ChREBP does not effectively homodimerize or bind to the ChoREs as a homodimer (22,24). Using a yeast-two hybrid screen, Max-like protein X (Mlx) was identified as a bHLH/LZ protein in liver that interacts with the bHLH/LZ domain of ChREBP (24).…”
mentioning
confidence: 99%
“…However, ChREBP does not effectively homodimerize or bind to the ChoREs as a homodimer (22,24). Using a yeast-two hybrid screen, Max-like protein X (Mlx) was identified as a bHLH/LZ protein in liver that interacts with the bHLH/LZ domain of ChREBP (24). Mlx is a member of the Myc/Max/Mad family of transcription factors, and similar to Max, it can serve as a common interaction partner of a tran-scription factor network (25)(26)(27).…”
mentioning
confidence: 99%